Relation Between PMBOK and IT Project Failure: The Billion Euro IT Disaster at NHS - Nazaruddin, Muhammad Daniel Emir; Mohamad Aizi Salamat; Aellisa Nabihah Azhan; Wan Nursyafiqah Sofia Mohd Haziman; Iskandar Dzulqarnain Shaiful Nizam; Nur Farrah Wahidah Md Shahril (Applied Information Technology And Computer Science, 2023)
The combination of technology and healthcare has brought in a new era in the healthcare industry, emphasizing the significance of effective project management. This study investigates the crucial significance of project management in the context of healthcare IT initiatives, as stated in the Project Management Body of Knowledge (PMBOK). It examines the National Programme for Information Technology (NPfIT) for the United Kingdom’s National Health Service (NHS) to demonstrate the implications of poor project management. With its significant financial ramifications and early closure, the NPfIT serves as a cautionary tale, emphasizing the importance of proper risk and cost management in healthcare IT efforts. The report finishes by emphasizing the critical role of project management in ensuring effective technology integration in healthcare.